2013
DOI: 10.1007/s11306-013-0585-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative structural profiling of trichome specialized metabolites in tomato (Solanum lycopersicum) and S. habrochaites: acylsugar profiles revealed by UHPLC/MS and NMR

Abstract: Many plants accumulate large quantities of specialized metabolites in secretory glandular trichomes (SGTs), which are specialized epidermal cells. In the genus Solanum, SGTs store a diverse collection of glucose and sucrose esters. Profiling of extracts from two accessions (LA1777 and LA1392) of Solanum habrochaites using ultra-high performance liquid chromatography–mass spectrometry (UHPLC/MS) revealed wide acylsugar diversity, with up to 11 isomers annotated for each individual elemental formula. These isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
126
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(136 citation statements)
references
References 37 publications
9
126
1
Order By: Relevance
“…Cultivated tomato produces primarily tri-and tetraacylated sucrose esters in the tip cell of the long multicellular "type I/IV" trichomes (14,29). Although two trichome apical cell-expressed BAHD acyltransferases that produce tri-and tetraacylsucroses from diacylsucroses were recently described (25,29), the enzymes that convert sucrose to diacylated sucrose have not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cultivated tomato produces primarily tri-and tetraacylated sucrose esters in the tip cell of the long multicellular "type I/IV" trichomes (14,29). Although two trichome apical cell-expressed BAHD acyltransferases that produce tri-and tetraacylsucroses from diacylsucroses were recently described (25,29), the enzymes that convert sucrose to diacylated sucrose have not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Acylsugar phenotypic diversity was observed for various wild tomato species and for accessions within S. pennellii and S. habrochaites (14,(24)(25)(26). For example, we recently demonstrated that introgression of a region of S. pennellii LA0716 from the top of chromosome 8 (IL8-1-1) causes increased accumulation of iC4-containing acylsucroses due to introduction of a gene encoding a truncated Leu feedback-insensitive isopropylmalate synthase (IPMS)-like enzyme (Sp-IPMS3) (15,26).…”
Section: Sl-asat2mentioning
confidence: 99%
See 3 more Smart Citations